2014
DOI: 10.1111/jeea.12110
|View full text |Cite
|
Sign up to set email alerts
|

A Global View of Cross-Border Migration

Abstract: This paper evaluates the global welfare impact of observed levels of migration using a quantitative multi‐sector model of the world economy calibrated to aggregate and firm‐level data. Our framework features cross‐country labor productivity differences, international trade, remittances, and a heterogeneous workforce. We compare welfare under the observed levels of migration to a no‐migration counterfactual. In the long run, natives in countries that received a lot of migration—such as Canada or Australia—are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 73 publications
3
57
2
1
Order By: Relevance
“…Decades passed before a series of follow-up studies confirmed the broad magnitude of the Hamilton and Whalley results with more refined macro models (Moses andLetnes 2004, 2005;Iregui 2005;Walmsley and Winters 2005;Klein andVentura 2007, 2009;van der Mensbrugghe and Roland-Holst 2009;surveyed in Clemens 2011). The mag-nitude of these estimates has been corroborated in a series of recent studies (Benhabib and Jovanovic 2012;Kennan 2013;di Giovanni et al 2015;Bradford 2015). Barriers to labor mobility, then, could cost the world on the order of half of potential production-leaving "trillion dollar bills on the sidewalk" (Clemens 2011).…”
Section: Macro Evidencesupporting
confidence: 54%
“…Decades passed before a series of follow-up studies confirmed the broad magnitude of the Hamilton and Whalley results with more refined macro models (Moses andLetnes 2004, 2005;Iregui 2005;Walmsley and Winters 2005;Klein andVentura 2007, 2009;van der Mensbrugghe and Roland-Holst 2009;surveyed in Clemens 2011). The mag-nitude of these estimates has been corroborated in a series of recent studies (Benhabib and Jovanovic 2012;Kennan 2013;di Giovanni et al 2015;Bradford 2015). Barriers to labor mobility, then, could cost the world on the order of half of potential production-leaving "trillion dollar bills on the sidewalk" (Clemens 2011).…”
Section: Macro Evidencesupporting
confidence: 54%
“…For example, the fall in the number of varieties available for consumption (Krugman, 1980) and productivity decreases due to fall in competition from abroad (Melitz, 2003), together with the presence of vertical production chains in the UK (Melitz and Redding, 2014), will most likely increase such losses. Furthermore, contrary to popular belief, ceasing migration flows between UK and other EU countries, one of the EU most basic principles, will also tend to decrease welfare not only in the source region but also in the destination one (di Giovanni, Levchenko, and Ortega, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…They find that, from a global perspective, migration ought to be much larger than it is today. Di Giovanni, Levchenko and Ortega (2014) quantify the welfare effects of international migration in a model that carefully incorporates total factor productivity and skill differences, within a Melitz (2003) framework of international trade with a home market effect. Docquier, Ozden, and Peri (2014) evaluate wage and employment gains from immigration and emigration in all OECD countries.…”
Section: Have Different Implications On the Labor Market Effects Of Imentioning
confidence: 99%